Does the government doing enough in providing affordable housing in Malaysia? - Omar, Ismail; Bahari, Azimuddin; Mohsen, Masfaliza (nil, 2020)
In neoclassical, market failure is a situation in which the allocation of goods and services by a free market is not Pareto efficient, often leading to a net loss of economic value. This mismatching between supply of and demand for land creates sky rocketing housing prices in the market. Since the Government is concerned in housing the nation, numerous housing programs to provide adequate affordable housing to meet the needs of the low income or the middle income households. Unfortunately, the country still lacks the supply of affordable homes to meet the demand. Supply of houses in the market is in abundance but they do not fall under the affordable category. Therefore, the existing Government policies and implementation of affordable housing need to be realigned accordingly.